2016
DOI: 10.1021/acs.energyfuels.5b02185
|View full text |Cite
|
Sign up to set email alerts
|

Modified Asphaltene Capillary Deposition Unit: A Novel Approach to Inhibitor Screening

Abstract: Asphaltene deposition in capillaries is a tool that has been used in an attempt to better understand asphaltene deposition in the field. However, data reproducibility and inhibitor ranking present some challenges with this technique. An improved asphaltene capillary deposition unit and a novel experimental protocol were developed to address these problems and are presented here. Using untreated Gulf of Mexico oil, the current study generated reproducible amounts of asphaltene deposit inside the capillary. It f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…[13][14][15][16][17] Numerous studies have been done on asphaltene aggregation, precipitation and deposition by coreflooding experiments, batch process, capillary tests and simulation. [18][19][20][21][22][23][24][25][26][27][28][29] For instance, Jafari Behbahani et al investigated asphaltene adsorption in a sandstone core sample during CO 2 injection and reported significant reduction of porosity and permeability due to deposited asphaltene in core sample. 18 Boek's group studied the aggregation and deposition of colloidal asphaltene in capillary flow and estimated deposit thickness by experiments and simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Numerous studies have been done on asphaltene aggregation, precipitation and deposition by coreflooding experiments, batch process, capillary tests and simulation. [18][19][20][21][22][23][24][25][26][27][28][29] For instance, Jafari Behbahani et al investigated asphaltene adsorption in a sandstone core sample during CO 2 injection and reported significant reduction of porosity and permeability due to deposited asphaltene in core sample. 18 Boek's group studied the aggregation and deposition of colloidal asphaltene in capillary flow and estimated deposit thickness by experiments and simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Gon and Fouchard used a custom-built asphaltene capillary deposition unit to evaluate the amount of asphaltene deposit inside the stainless-steel capillary unit under high temperature and pressure. 27 However, in most of these works, asphaltene destabilization and aggregation behaviors were only investigated by several macroscopic parameters, such as pressure drop, porosity and permeability. They did not give direct visualization and analysis on asphaltene aggregation and precipitation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, it was shown that the addition of asphaltene inhibitors did not necessarily prevent or reduce the deposition. However, in some cases, it worsened the problem. ,, …”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach was recommended by Gon et al 58 to cut the capillary into segments before solvent wash and quantification. This approach was also used in the study by Kuang et al 86 After the deposition experiment, the capillary tube was cut into 10 similarly sized (1 ft) segments, and the amount of asphaltene was quantified for each section.…”
Section: Test Methods For Asphaltene Inhibitorsmentioning
confidence: 99%
“…Trials of asphaltene inhibitors in the field are costly and time-consuming. Hence, it is necessary to find simple laboratory-based techniques that may provide information on the mechanism of action of asphaltene inhibitors and their performance (Gon and Fouchard, 2016;Lin et al, 2017;Marcano et al, 2015). Such techniques would enable facile pre-screening of inhibitors prior to field trials.…”
Section: Introductionmentioning
confidence: 99%